Significant suppression of phonon transport in polar semiconductors owing to electron-phonon-induced dipole coupling: An effect of breaking centrosymmetry. (January 2022) - Liu, Te-Huan; Zhou, Jiawei; Xu, Qian; Qian, Xin; Song, Bai; Yang, Ronggui
Abstract: Thermal resistance induced by long-range electron-phonon interaction is often considered negligible. Here, by combining ab initio calculations with analytical modeling, we show that the scattering rate of acoustic phonons due to the electron-phonon-induced dipole (EPID) interaction varies asymptotically as the reciprocal of the phonon wavevector (∝ q –1 ), and surpasses the short-range deformation-potential scattering as the wavevectors reduce to tens of reciprocal centimeters. This strong EPID coupling can significantly suppress the thermal conductivity in wurtzite zinc oxide, which originates from the absence of a mirror plane perpendicular to the c -axis that breaks the inversion symmetry of the out-of-plane vibrational modes. In contrast, such an effect does not occur in the zinc-blende gallium arsenide because no piezoelectric field can be generated along the three principal axes. This work highlights the effect of centrosymmetry breaking on tailoring phonon transport in polar semiconductors. Graphical abstract: Image 1 Highlights: Electron-phonon-induced dipole coupling induces the acoustic phonons a divergent scattering rate. An analytical model is developed to verify the asymptotic behaviors of the phonon scattering rate at long-wavelength limit. This work highlights the linkage between phonon thermal transport and centrosymmetry breaking.